Pole vault - Vitali Petrov's methodology - Petrov, V. (2010)
For Petrov pole vault consists of three main parts: gymnastics, run and pole vault technique. He explains all three parts as well as the development from a beginner (age of 13-15)to a top level pole vaulter (24-28).